Aesthetic-Receptive and Critical-Creative in Appreciative Reading - Titin Setiartin (JETL (Journal of Education, Teaching and Learning), 2017)
Reading is a process of aesthetically appreciative receptive to emphasize critical-creative reading activities. Metacognitively students understand, address any and explore the idea of the author in the text. Students responded, criticize, and evaluate the author's ideas in the text. At this stage, students can construct their post read text into other forms (new text). The aim of this strategy equips students to understand the meaning of the story, explore ideas, responding critically, and creatively pouring backstory idea. Reading strategies aesthetically-critical-creative receptive grabbed cognitive, effective, and psychomotor toward literacy critical reading and creative writing. Read appreciative included into the activities of reading comprehension. This activity involves the sensitivity and ability to process aesthetically-receptive reading and critical-creative. Readers imagination roam the author to obtain meaningful understanding and experience of reading. Some models of reading comprehension proposed experts covering the steps before reading, when reading, and after reading. At that stage to enable students after reading thinking abilities. Activities that can be done at this stage, for example, examine the back story, retell, make drawings, diagrams, or maps the concept of reading, as well as making a road map that describes the event. Other activities that can be done is to transform our student's text stories through reinforcement form illustrated stories into comic book form, for example (transliteration).